2021
DOI: 10.1108/pm-09-2020-0055
|View full text |Cite
|
Sign up to set email alerts
|

Student accommodation, environmental behaviour and lessons for property managers

Abstract: PurposeDespite awareness of climate change for over 3 decades, per capita energy and water consumption increase and environmental impacts grow. The built environment contributes around 40% of total global greenhouse gas (GHG) emissions; action is vital. Whilst building code standards have increased, rating tools and technology to reduce energy and water consumption are developed; environmental impact grows because of human behaviour. In the tertiary education sector, student accommodation constitutes a large p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 68 publications
(120 reference statements)
0
6
0
Order By: Relevance
“…In the business research area focus is on the development of digital services (e.g., "Service design for the sustainable behavior modeling: Smart schedule", [32]). Equally important are social research areas, with co-living topics ("Co-living & Productive space usage"), sociology and behavior ("Occupant pro-environmental choice and behavior" [33]), and health, for instance with the monitoring of quality of indoor environment (with the project "Allergen free indoor environment with innovative ventilation strategies", resulting in a recent publication [34]).…”
Section: Resultsmentioning
confidence: 99%
“…In the business research area focus is on the development of digital services (e.g., "Service design for the sustainable behavior modeling: Smart schedule", [32]). Equally important are social research areas, with co-living topics ("Co-living & Productive space usage"), sociology and behavior ("Occupant pro-environmental choice and behavior" [33]), and health, for instance with the monitoring of quality of indoor environment (with the project "Allergen free indoor environment with innovative ventilation strategies", resulting in a recent publication [34]).…”
Section: Resultsmentioning
confidence: 99%
“…However, there exists a scarcity of research pertaining to proenvironmental behavior on university campuses. Besides, prior academic work examining on-campus pro-environmental engagement of university students mostly focused on undergraduates' waste management practices (e.g., recycling, and waste separation) (Chao et al, 2023;Cho, 2019;Largo-Wright et al, 2012;Moqbel et al, 2020) or their environmentally friendly behaviors in specific settings (e.g., dormitories) of campus (Mokrzecka & Nowak, 2019;Thondlana & Hlatshwayo, 2018;Wilkinson & Zalejska Jonsson, 2021). For example, in Cho's (2019) paper, findings suggested that positive attitudes towards recycling, perceived control, negative anticipated emotions, and self-determined motivation lead to on-campus recycling intentions.…”
Section: On-campus Pro-environmental Behaviorsmentioning
confidence: 99%
“…Product innovation is conceptualised in the housing sub-sector to include improved facilities that offer fully furnished and provide privacy, security and a comfortable living experience (Najib et al, 2011;Adegoke et al, 2021). The Provision of these products is aimed to form the personal character, improve the thought and behaviour of the student, enhance intellectual competence and provide a serene environment for students (Wilkinson and Jonsson, 2021;Hassanain, 2008). On the other hand, marketing innovation focuses on emerging student preferences, such as access to improved individual separate rooms, washrooms, laundry, Internet access and provision of study areas (Sawyerr and Yusof, 2013).…”
Section: A Conceptualisation Of Innovation In Student Housingmentioning
confidence: 99%